Development And Validation Of Stability Indicating RP-HPLC Method For Determination Of Ceritinib - Adhao, Vaibhav Suresh; Sharma, J; Thakre, M (INDONESIAN JOURNAL OF PHARMACY, 2017)
A new, simple, specific, accurate and precise RP-HPLC method was developed for determination of Ceritinib. In the present study, stress testing of Ceritinib was carried out according to ICH guidelines Q1A (R2). Ceritinib was subjected to stress conditions of hydrolysis, oxidation, photolysis and neutral decomposition. Extensive degradation was found to occur in acidic, condition. Mild degradation was observed in basic and at thermal conditions. Successful separation of drug from degradation products formed under stress conditions was achieved on a Hypersil BDS C18 column (250 mm Ã 4.6 mm, 5.0 Î¼ particle size) using acetonitrile: acetate buffer (pH 3.7 Â± 0.05) (50:50 v/v), at a flow rate of 1.0 mL/min and column was maintained at 40ËC. Quantification and linearity was achieved at 272 nm over the concentration range of 5 - 100 Î¼g/mL for Ceritinib. The method was validated for specificity, linearity, accuracy, precision, LOD, LOQ and robustness.